The borderlands between punitive and non-punitive transitional justice: distinct elites and diverging patterns of import/export - Christensen, Mikkel Jarle (International journal of transitional justice, 2020)
Transitional justice consists of different ideals and practices that both coexist and conflict. This article investigates the socio-professional borderlands between punitive and non-punitive transitional justice initiatives by analyzing elites working in either international criminal courts, or truth and reconciliation commissions. While they were marginally linked, the professional practices of these elites were structured by their distinct positions in the larger market of transitional justice. Professionals of international criminal law were tied to international institutions from where they were often on the exporting side of particular internationalized, punitive norms and practices. In contrast, professionals involved with truth and reconciliation were closely connected to states that structured their import/export of internationalized, non-punitive initiatives. Punitive and non-punitive transitional justice was characterized not only by competing ideals and practices, but was embedded in distinct elites whose proximity to or distance from the state structured the circulation of transitional justice ideas and practices.